Postdural puncture headache: evidence-based review for primary care - Olufemi B. Omole; Gboyega A. Ogunbanjo (South African Family Practice)
The promotion of epidural and spinal blocks as preferred and safe techniques for Caesarean section and the use of lumbar puncture for diagnostic and therapeutic purposes place patients at risk of developing postdural puncture headache (PDPH). This article reviews the literature for evidence that provides an approach to diagnosis and management of this condition for the primary care physician. A dull and throbbing, bilateral headache associated with changes in posture (worsened by sitting and standing, and better lying down), that develops within seven days of a lumbar puncture or an inadvertent dural puncture must raise the suspicion of PDPH. The exact causative mechanism is unclear but symptoms of PDPH are generally attributed to excessive loss of cerebrospinal fluid (CSF). The risk of PDPH is increased with the use of cutting and large-bore needles, and with horizontal orientation of the needle bevel. Given that symptoms overlap, other organic causes of headache such as intracerebral/subdural haemorrhage, pneumocephalus, central nervous system infections, adverse effects of anticoagulants and functional headaches such as migraine must be excluded. Although the initial management of PDPH comprises several conservative interventions, evidence is only available for the effectiveness of the usage of caffeine, analgesics, gabapectin, hydrocortisone, dexamethasone and cosyntropin. Epidural blood patch (EDBP) offers the most favourable outcomes for patients who fail to respond to conservative management. However, given the lack of skills for performing EDBP in primary care, such patients should be referred to secondary or tertiary level of care.